Applying Multi-Criteria Decision Making Technique in Hospitality Quality Management System - Kit, Yeng Sin; Mun, Chong Sin (Human Resource Management Academic Research Society (HRMARS), 2019)
This study evaluates the importance of quality management (QM) critical success factors (CSFs) within the context of Malaysian hotel firms. Primary criteria to evaluate QM CSFs were determined through literature survey and multi-criteria decision making (MCDM) technique assisted by Decision-Making Trial and Evaluation Laboratory (DEMATEL)-based analytical network process (ANP) (D-ANP). D-ANP is integrated to allow the calculation of importance level, weights of all dimensions and indicators, as well as significances. The findings demonstrated the way hotels can be evaluated and ranked, based on the relationships between and among the contexts and variables. The research findings will assist the policymakers (Ministry of Tourism) to formulate policies and data of QM best practices that will ensure the success of hotel firms.